2015
DOI: 10.1158/1055-9965.epi-15-0103
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and Ethnic Variations in Breast Cancer Risk Factors, Gail Model Risk Estimates and Mammographic Breast Density

Abstract: (95% CI, 1.18-1.51) among never or former smokers (p-trend < 0.001). This positive trend for PCa mortality was mainly observed among men with BMI measured more than 5 years before diagnosis, and among those age >65 years old at diagnosis. Compared with never smokers, current smokers had significantly elevated risk of PCa death, with a HR of 1.92 (95% CI, 1.52-2.43) regardless of the time of measurement, age at diagnosis and BMI. After further adjusting for tumor stage and grade, the association between BMI, sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Immigrant groups compared to U.S.-born natives fare worse across many health conditions, including diabetes, heart disease, depression, and cancer [11,12], and display complex determinants influencing the health paradox [13]. In fact, disease manifestation (e.g., breast cancer) occurs the longer immigrants reside in the U.S. [14,15]. Speculations to the disparate health conditions of immigrant groups may be related to health care access and utilization [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Immigrant groups compared to U.S.-born natives fare worse across many health conditions, including diabetes, heart disease, depression, and cancer [11,12], and display complex determinants influencing the health paradox [13]. In fact, disease manifestation (e.g., breast cancer) occurs the longer immigrants reside in the U.S. [14,15]. Speculations to the disparate health conditions of immigrant groups may be related to health care access and utilization [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of the studies assessing breast density and cancer risk have been conducted among White women, with limited inclusion of minority populations . The data on Hispanic women are more limited . Results are conflicting .…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] The data on Hispanic women are more limited. 16,17 Results are conflicting. 15,16,18,19 Razzaghi et al 12 found that White cases and controls had a greater percentage of "extremely dense" and "heterogeneously dense" breasts compared with African-American cases and controls.…”
mentioning
confidence: 99%
See 1 more Smart Citation